A Meta-Analysis of Language Policy on Bilingual Education in Indonesian Universities: Implication for Multicultural Education and Internationalization - Amirullah Abduh; Sulaiman Samad; Rosmaladewi Rosmaladewi (Universitas Negeri Makassar, 2022)
The study aims to portray the implementation of bilingual language policy and its implications for multiculturalism and internationalization of higher education. The meta-analysis research design enables the researchers in this study to search the available published public documents that are relevant for this study. The result of the study indicates that the implementation of language policy on bilingual education in higher education contexts facilitates the preservation of local and national identities, fosters multicultural pedagogical interaction, and supports the internationalization of universities. This study recommends further in-depth investigation in a multicultural setting with longitudinal approach.